Analisis Faktor Yang Mempengaruhi Belanja Daerah Kabupaten Sidoarjo Tahun Anggaran 2009 -2018 - Bemby Agung Pratama (Fakultas Ekonomi Universitas Panca Marga, 2021)
Abstract: This study aims to analyze the effect of economic growth, PAD and DAU on Regional Expenditures in Sidoarjo Regency in 2009-2018. This research is a quantitative study with a descriptive and associative research design. The data used are PAD time series data, balance funds, and regional expenditure on the website of the Ministry of Finance's DGT and the Central Statistics Agency (BPS) Sidoarjo Regency in 2009-2018. The data technique is secondary by collecting some references from the website of the Ministry of Finance and BPS Sidoarjo. Data analysis techniques use descriptive statistics, classical assumption tests, simple and multiple tests, regression testing and partial hypothesis testing (t test) and simultaneous hypothesis testing (F test ) with the help of SPSS software. The results of the analysis show that the partial (t) test of the General Allocation Fund (DAU) has a significant effect on regional spending, while economic growth and local revenue (PAD) have no significant effect on regional spending. By testing (f) simultaneous economic growth, local revenue (PAD) and general allocation funds (DAU) have a significant effect on regional spending.